Geomagnetic disturbances at F1-layer heights under different solar activity conditions over Norilsk - Kushnarenko G.P.; Yakovleva O.E.; Kuznetsova G.M. (Solar-Terrestrial Physics, 2019)
We analyze the influence of geomagnetic disturbances on the electron density Ne at Norilsk ionospheric station (69° N; 88° E) at F1-layer heights (120–200 km). For the analysis, we have selected 25 moderate and weak geomagnetic disturbances for two seasons — spring and fall — of 2003–2014. Using the Ne values obtained from measurements made with the Norilsk digisonde during this period, we analyze Ne variations during geomagnetic disturbances in spring and fall for a long period of time. We determine the effect of spring-fall asymmetry occurring in all solar activity phases and manifesting itself in a significant decrease in the electron density during the main phase of fall storms at all heights in comparison with quiet days: up to 2.6 times at a height of 200 km and slightly less at lower heights. This phenomenon is not observed during spring disturbances: Ne variations are much weaker.